Evaluate the effect of L-valine on linear–nonlinear optical and electrical properties of BTCA crystal to identify photonic device applications. (6th June 2016) - Anis, Mohd; Hussaini, S. S.; Shirsat, M. D.; Muley, G. G.
Abstract : In this study, pure andl -valine (LV)-doped bis-thiourea cadmium acetate (BTCA) crystals have been grown by slow solution evaporation technique. For the first time, LV has been used as a dopant to tune the optical (linear and third-order non-linear optical) and electrical properties of BTCA crystal which are vital for various integrated optic device applications. The UV-visible spectral analysis has been performed in the range of 200–900 nm to determine the optical transparency of grown crystals. The Z-scan (open and closed apertures) studies were undertaken at 632.8 nm to ascertain the nature of third-order non-linearity in grown crystals. The third-order non-linear optical parameters such as non-linear refraction ( n 2 ), absorption coefficient ( β ) and susceptibility ( χ 3 ) of grown crystals have been calculated. The susceptibility ( χ 3 ) of pure and LV-doped BTCA crystal is found to be 2.58 × 10 −4 esu and 3.34 × 10 −4  esu, respectively. The electrical studies have been carried out to analyse the dielectric constant, dielectric loss, ac resistivity and ac conductivity of pure and LV-doped BTCA crystals.